Effect of formulation on the quality of frozen bread dough - Salas-Mellado,Myriam M. (2003)
The main objective of this work was to determine the influence of formulation on the stability of bread dough during frozen storage. Bread doughs containing gluten and trehalose were submitted to mechanical freezing at -30° C and stored frozen for 45 days. Two types of instant yeast were tested: (A) for sweet doughs and (B) for savoury doughs. Specific volume was significantly affected by the yeast type, type A showing better effect than type B. Frozen storage of the doughs negatively affected the specific volume, crumb hardness and technological score of the bread. The addition of 10% trehalose had a beneficial effect on the cell survival rate for both the yeasts.